Effect of package spacing on convective heat transfer from thermal sources mounted on a horizontal surface. (5th March 2018) - Ali, R.K.; Refaey, H.A.; Salem, M.R.
Highlights: Three-dimensional analysis of an inline module composed of two thermal sources. Applicable range of air velocity ( 2464 ⩽ Re L ⩽ 16, 430 ), package spacing ratio ( 1 ⩽ s / L ⩽ 3 ). The gap effect on upstream thermal source temperature is vanished at s/L = 3. Increasing package spacing more than 3 has almost no additional enhancement on the downstream thermal source. Nusselt number correlations for the module were presented. Abstract: This work introduces a three-dimensional analysis of an inline module composed of two thermal sources using ANSYS-FLUENT Computational Fluid Dynamics (CFD) package. The effect of package spacing ratio (1 ≤  S  ≤ 3) on the heat transfer coefficient of the upstream (UTS) and downstream (DTS) thermal sources within Reynolds number range of 2464 ⩽ Re L ⩽ 16, 430 are considered. The predictions are compared with the experiments performed on air wind tunnel with two thermal sources mounted on its horizontal surface within Reynolds number range of 4848 ⩽ Re L ⩽ 13, 635 . The numerical results are compared and validated with the experimental results and a good agreement is obtained. Compared to a single thermal source (STS), it is observed that the reduction in the average Nusselt number of the UTS and DTS is 26.3% and 35.6%, respectively, at S =  1. This reduction decreases to 4.9% and 12.6%, respectively, at S =  3. Finally, the present study aims to extend the printed circuit boards designers with average Nusselt number correlations for the UTS and DTS as a function of Reynolds number and package spacing within 2464 ⩽ Re L ⩽ 16, 430 and (1 ≤  S  ≤ 3).